Health professions school applicant experiences of discrimination during interviews. (4th May 2023) - Chatterjee, Avik; Dunleavy, Spencer; Gonzalez, Tiffany; Benson, Jalen; Henault, Lori; MacIntosh, Alexander; Goodell, Kristen; Witzburg, Robert; Paasche-Orlow, Michael
Abstract: Background: Bias pervades every aspect of healthcare including admissions, perpetuating the lack of diversity in the healthcare workforce. Admissions interviews may be a time when applicants to health profession education programs experience discrimination. Methods: Between January and June 2021 we invited US and Canadian applicants to health profession education programs to complete a survey including the Everyday Discrimination Scale, adapted to ascertain experiences of discrimination during admissions interviews. We used chi-square tests and multivariable logistic regression to determine associations between identity factors and positive responses. Results: Of 1115 respondents, 281 (25.2%) reported discrimination in the interview process. Individuals with lower socioeconomic status ( OR : 1.78, 95% CI [1.26, 2.52], p  = 0.001) and non-native English speakers ( OR: 1.76, 95% CI [1.08, 2.87], p  = 0.02) were significantly more likely to experience discrimination. Half of those experiencing discrimination (139, or 49.6%) did nothing in response, though 44 (15.7%) reported the incident anonymously and 10 (3.6%) reported directly to the institution where it happened. Conclusions: Reports of discrimination are common among HPE applicants. Reforms at the interviewer- (e.g. avoiding questions about family planning) and institution-level (e.g. presenting institutional efforts to promote health equity) are needed to decrease the incidence and mitigate the impact of such events.